(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
Rregardless of sports, the increase in muscle strength exceeds rate of increase in muscle mass. Wrestling leads to reliable annual increase in chest circumference and body weight. Doing so power sport, like freestyle wrestling, is the external factor which largely affects the morpho functional state of the body of young people